2023
DOI: 10.3390/ph16071004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mTOR Signalling Pathway and Its Inhibitory Scope in Cancer

Abstract: Mechanistic target of rapamycin (mTOR) is a protein kinase that regulates cellular growth, development, survival, and metabolism through integration of diverse extracellular and intracellular stimuli. Additionally, mTOR is involved in interplay of signalling pathways that regulate apoptosis and autophagy. In cells, mTOR is assembled into two complexes, mTORC1 and mTORC2. While mTORC1 is regulated by energy consumption, protein intake, mechanical stimuli, and growth factors, mTORC2 is regulated by insulin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 170 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…The serine–threonine protein kinase known as mammalian target of rapamycin or mechanistic target of rapamycin (mTOR) plays a crucial role in regulating cellular metabolism, growth, cell proliferation, survival, and gene expression. Recent studies have shown that over 70% of malignancies exhibit hyper activated mTOR pathways ( Mir et al, 2023 ). In recent years, several mTOR inhibitors have been developed with the aim of treating different cancers.…”
Section: Effect Of Flavonoids On Different Signalling Pathways In Cancermentioning
confidence: 99%
“…The serine–threonine protein kinase known as mammalian target of rapamycin or mechanistic target of rapamycin (mTOR) plays a crucial role in regulating cellular metabolism, growth, cell proliferation, survival, and gene expression. Recent studies have shown that over 70% of malignancies exhibit hyper activated mTOR pathways ( Mir et al, 2023 ). In recent years, several mTOR inhibitors have been developed with the aim of treating different cancers.…”
Section: Effect Of Flavonoids On Different Signalling Pathways In Cancermentioning
confidence: 99%